PENGARUH PELAYANAN TRANSAKSI GADAI DAN SANKSI KETERLAMBATAN PELUNASAN TERHADAP KEPUASAN NASABAH GADAI EMAS DI BMT TUNAS HARAPAN SYARIAH CABANG PRINGGASELA LOMBOK TIMUR NTB - Nadya Desi Saputri; Din Hary Fitriadi; Suriani (Jurnal Perbankan Syariah, 2023)
Abstract This study aims to determine how much influence pawn transaction services and late payment penalties have on customer satisfaction of gold pawning at BMT Tunas Harapan Syariah Pringgasela Branch. This research uses quantitative research methods. Which is processed using the IBM SPSS 22 application. While data collection uses a questionnaire (questionnaire). The sample technique used in this study is using simple random sampling, namely by taking samples randomly. The results of this study indicate that based on the results of the T test data analysis that the Transaction Service variable (X1) has a value of tcount > ttable (14,949 > 1,998) and the variable Late Sanctions (X2) (2,863 > 1,998) where both tcounts are greater than ttable. This proves that there is a partial influence between Pawn Transaction Services (X1) and Late Payment Sanctions (X2) on Gold Pawn Customer Satisfaction at BMT Tunas Harapan Syariah Branch of Pringgasela. And based on the results of the F Test data analysis, it shows that simultaneously the variables (X1) and (X2) have a significant effect on Gold Pawn Customer Satisfaction at BMT Tunas Harapan Syariah Pringgasela Branch (Y). This can be seen by looking at the significant value of sig 0.00 <0.05.